History of Local Self-Government Bodies of Dilijan Province in 1918-1920 - Asatryan, Anna (History and Culture, 2025)
The article highlights the history of the creation and activities of the first provincial local self-government bodies in Armenian reality. The important significance of the establishment of the provincial local self-government in Dilijan in February 1918 in a difficult political situation and the ways of the latter to overcome the crisis of the administration of the province with a mixed population, which was associated with inter-ethnic conflicts, food procurement and other issues of socio-economic and security significance, were presented. It was found out why the government of the country changed the main staff of local self- government after the declaration of independence of the RA․ In the article we referred to the democratically organized local self-government elections on September 21, 1919, the pre-election and post-election processes. We also pointed out the successful initiatives and inactions of the executive body of local self-government, which had a direct impact on changing the quality of life of the population of the province, because schools, hospitals, orphanages, food outlets and other important institutions were under the authority of the department.The reasons for the abnormal functioning of local self-government in Dilijan province, which were largely due to the anti-state actions of the Bolsheviks, intra-party conflicts and other factors, were highlighted.
Keywords: Dilijan; local self-government body; council; department; democracy; independence; elections; party